Peripheral CD4 T follicular cells induced by a conjugated pneumococcal vaccine correlate with enhanced opsonophagocytic antibody responses in younger individuals. Issue 7 (11th February 2020) - Sterrett, Sarah; Peng, Binghao J.; Burton, Robert L.; LaFon, David C.; Westfall, Andrew O.; Singh, Suddham; Pride, Michael; Anderson, Annaliesa S.; Ippolito, Gregory C.; Schroeder, Harry W; Nahm, Moon H.; Krishna Prasad, A.; et al.
Abstract: Background: PCV13 (conjugated polysaccharide) and PPSV23 (polysaccharide only) are two licensed vaccines targeting S. pneumonia e. The role of CD4 T-cell responses in pneumococcal vaccines among healthy participants and their impact on antibodies is not yet known. Methods: Ten adults (5 old and 5 young) received PCV13 (prime) and a year later PPSV23 (boost). Blood samples were collected prior to and multiple time points after vaccination. CD4 T cells responding to CRM197, polysaccharide (PS), CRM197 conjugated polysaccharide (CPS), PCV13 and PPSV23 vaccines were measured by flow cytometry. Serum antibodies were analyzed via multiplex opsonophagocytosis (MOPA) and pneumococcal IgG assays. Results: Vaccine-specific CD4 T cells were induced in all ten vaccinees post PCV13. Older vaccinees mounted higher peak responses and those specific for PCV13 and conjugated PS-1 were more polyfunctional compared to the younger group. Vaccine-elicited peripheral T follicular helper (Tfh) cells were only detected in the younger group who also exhibited a higher fold change in OPA titers post both vaccines. Importantly, Tfh cells following PCV13 correlated only with PCV13 serotype specific OPA titers after PPSV23 vaccination. Conclusions: These findings demonstrate age related differences in immune response and the potential importance of Tfh in modulating functional antibody responses following pneumococcal vaccination.